Defoliation Capability of Poplar Defoliator, Clostera cupreata Butler (Lepidoptera: Notodontidae) - Ahmad, Mukhtar; Mishra, Ramakant; Jamal Ahmad, M. D.; Pandey, Rajiv (Indian Forester, 2002)
Defoliating capability of poplar defoliator, Clostera cupreata was studied by exposing measured leaf to different larval instars. Females were found to defoliate more as 0.99, 8.82, 12.65,22.13, and 103.88 cm2 ofleafwas consumed by a larva from first to fifth ins tar respectively, whereas a male larva was able to feed 0.96, 5.99, 7.67, 19.30 and 48.63 cm2 of poplar foliage from first to fifth instar respectively. Relationship between food consumption and growth rate of larva was established using various parameters including growth rate, relative growth rate, consumption rate, consumption index, and efficiency of conversion of ingested food.